A high-rate and stable nitrogen removal from reject water in a full-scale two-stage AMX® system - Minki Jung (IWA Publishing, 2021)
This paper reports long-term performance of a two-stage AMX® system with a capacity of 70 m3/d treating actual reject water. An air-lift granulation reactor performed partial nitritation (PN–AGR) at an average nitrogen loading rate (NLR) of 3.1 kgN/m3-d, producing an average effluent NO2-–N/NH4+–N ratio of 1.04. The average nitrogen removal rate of the system was 3.91 kgN/m3-d following an anaerobic ammonium oxidation (Anammox) stage moving bed biofilm reactor (A–MBBR). Although the total nitrogen concentrations in the reject water fluctuated seasonally, overall nitrogen removal efficiency (NRE) of the two-stage AMX® system was very stable at over 87%. The two-stage AMX® system, consisting of a PN–AGR followed by an A–MBBR, operated at a stable NLR of 1.86 kgN/m3-d (1.64 kgN/m3-d including the intermediate tank), which is 1.8 times higher (1.6 times including the intermediate tank) than other commercialized single-stage partial nitritation/Anammox (PN/A) processes (which operate at a NLR of about 1 kgN/m3-d). The PN–AGR was affected by high influent total suspended solids (TSS) loads, but was able to recover within a short period of 4 days, which confirmed that the two-stage PN/A process is resilient to TSS load fluctuations.